Elevated red blood cell distribution width levels predict depression after intracerebral hemorrhage: A 3-month follow-up study - Zhou, Xianping; Li, Yaqiang; Sun, Zhongbo; Mu, Li; Ma, Yaoyao (Frontiers in Neurology, 2023)
Objectives: Inflammation plays a vital role in the development of depression after intracerebral hemorrhage (ICH), while red blood cell distribution width (RDW) has been identified as a marker of inflammatory-related diseases. The present study aimed to evaluate the relationship between RDW and depression after ICH. Methods: From prospective analyses of patients admitted to our department between January 2017 and July 2022, ICH patients with complete medical records were evaluated. The 17-item Hamilton Depression Scale (HAMD-17) was used to measure depressive symptoms at 3 months after ICH. Patients were given the DSM-V criteria for diagnosis of post-ICH depression. Results: Of the 456 enrolled patients, 99 (21.71%) patients were diagnosed with PSD at 3-months follow-up. The results also revealed significantly higher level of RDW in patients with depression (13.70 (IQR 13.24-13.89) vs.13.56 (IQR 12.60-13.75), P＜0.001) at admission than patients without depression. In multivariate analyses, RDW was an independent predictor of depression after ICH at 3 months [OR:1.453 (95% CI, 1.167-1.965), P=0.019]. After adjustment for potential confounding factors, the odds ratio of depression after ICH was 3.118 (95% CI: 1.476-3.378, P = 0.023) for the highest tertile of RDW compared with the lowest tertile. With an AUC of 0.665 (95% CI, 0.610-0.720), RDW demonstrated a significantly greater discriminatory ability as compared with CRP, WBC, and IL-6. The optimal cut-off value of RDW as an indicator for prediction of depression after ICH was projected to be 13.69, which yielded a sensitivity of 61.7% and a specificity of 69.6%. Conclusions: Elevated level of RDW was associated with post-ICH depression at 3 months, suggesting that RDW might be a useful Inflammatory markers to predict depression after ICH.